PATH-38. APC MUTATION AS A DRIVER ONCOGENE IN NON-CTNNB1 MUTANT ADAMANTINOMATOUS CRANIOPHARYNGIOMAS. (12th November 2021) - Hong, Christopher; Erson-Omay, Zeynep; Omay, S Bulent
Abstract: Craniopharyngiomas arise from the embryonic remnants of Rathke's pouch in the craniopharyngeal duct. Their invasive capacity and geographic proximity to the optic apparatus, pituitary gland and stalk, third ventricle, and the hypothalamus can cause progressive visual, hormonal, and neurological deficits and transform these lesions into behaviorally malignant tumors. The classic subtypes of craniopharyngiomas, adamantinomatous and papillary, have conventionally been approached similarly in regards to therapeutic strategies. However, recent exome sequencing studies have revealed mutually exclusive pathways for their genetic origins. Recurrent mutations in BRAF ( V600E ), a regulator of MAP kinase/ERK signaling pathway have been observed in 95% of papillary craniopharyngiomas and may be amenable to targeted therapies with BRAF inhibitors. However, CTNNB1 mutations are observed in only 75%–96% of adamantinomatous craniopharyngiomas, revealing a gap in the classic genetic-histological correlation. We describe a 74-year-old male who underwent resection of a craniopharyngioma with suprasellar and third ventricular involvement. The pathology demonstrated adamantinomatous craniopharyngioma with aberrant nuclear beta-catenin activity on immunohistochemistry. Whole-exome sequencing, performed in accordance with an institutional review board-approved protocol on the tumor and blood, revealed wildtype CTNNB1 but notably two somatic stop-codon mutations in APC (rs786201856:c.C793T:p.R265X and rs587779780:c.1159T:p.R387X), considered pathogenic variants in other reported cancer types. Loss of APC leads to constitutive activation of the Wnt signaling pathway, similar to the observed downstream effects of activating CTNNB1 mutations in adamantinomatous craniopharyngioma. Our case suggests that craniopharyngiomas may arise from somatic loss of APC, which previously was only described in a handful of individuals with familial adenomatous polyposis, harboring germline APC mutations. This report adds new insight into the pathogenesis of adamantinomatous craniopharyngiomas, particularly those that are otherwise wildtype for CTNNB1 . Based on accumulating evidence, we propose that along with BRAF and CTNNB1, APC should also be routinely checked in cranipharyngiomas, especially if the former two have been negative.